Análisis crítico del discurso aplicado en la fidelización de la fuerza de ventas de las empresas multinivel que operan en la ciudad de Quito - Godoy Padilla, Mercy Angélica (2015)
The purpose of this research is to determine the main discursive features and elements that aim to persuade, entice and retain sales force of multilevel companies in Quito. The method used is qualitative, the same one, it allows you to analyze the elements used in speeches by Yanbal, Oriflame and Herbalife. They were used as primary source of information semi-structured interviews, which were conducted at 25 sellers of companies mentioned above. Once the respective analysis is done, they could be determined the influence of the discourse of network members in their loyalty. Multilevel use well done speeches that contain embedded promises focus on creating expectations on satisfaction that will overtake to those who opt for this alternative like an income source, as well as those who are already part of the same, ie it would become a platform to fulfill dreams. This will not always be reached because the sales force suffers disappointments along the way, due it´s not expose true and complete information, but rather one that serves the interests of economic entities that issue. Taking into consideration the nature of these companies., the speech employed is not only aims to attract and retain your sales force, but also prepares the necessary conditions for accepting to work knowing that they don´t have labor protection, which could be a way to evade this type of work obligations.